The relationship between Diabetes mellitus and deaths from Covid-19: an integrative review (Research, Society and Development, 2022)
Objective: To analyze and describe the available evidence, in the scientific literature, about the association between diabetes mellitus associated with deaths from Covid-19. Method: Integrative literature review, with a search for articles published between the years 2020 and 2021, in the LILACS, PubMed, MEDLINE and The Preprint Server for Health Sciences (medRvix) databases. The results were organized in synoptic tables, and the data were extracted by two independent researchers. Results: Initially, 225 publications were found. After applying the filters, there were a total of 18 publications that met the inclusion criteria proposed for this study. From the reading of the selected works, it is possible to observe the close relationship between diabetes mellitus and severe cases of covid-19 and the high mortality rate as an outcome of these cases. Conclusion: There is an imperative need that is shown to health professionals to understand the pathophysiology of the clinical conditions of diabetes mellitus and the SARS-CoV-2 virus, separately and concomitantly, in order to better understand the clinical condition that the patient presents. with covid-2, which allows, in this way, the best targeting of the therapeutic management.